Patchouli Oil Quality In Various Methods of Drying Plant Materials Nilam (Pogostemon cablin Benth) - Darmadi Erwin Harahap; Eka Nurwani Ritonga; Qorry Hilmiyah Harahap; Msy.Nurhalimah; Muhammad Darwis; Dodi Syahrin (International Journal of Science and Environment (IJSE), 2026)
This study aims to determine the effect of various drying methods on patchouli oil yield and patchouli content. The study used a Completely Randomized Design (CRD) with four treatments, namely P₀ = without drying (control), P₁ = drying under direct sunlight, P₂ = drying using a paranet, and P₃ = drying using a tarpaulin. The parameters observed included patchouli oil yield and patchouli content. The results showed that the drying method significantly affected patchouli oil yield and patchouli content. The highest oil yield was obtained in the P₂ treatment (drying using a paranet) with an average of 2.61%, while the lowest yield was obtained in the P₀ treatment (without drying) at 1.82%. The highest patchouli content was also found in the P₂ and P₃ treatments at 30%, while the lowest was found in the P₀ treatment at 25%. Thus, the drying method using paranet is the best treatment in increasing patchouli oil yield and patchouli content.